The Application of Excretion System E-Module to Improve Science Literacy Skills - Chairunnisa, Friska; Maryuningsih, Yuyun; Maknun, Djohar (Biosfer: Jurnal Tadris Biologi, 2021)
The research aims to analyze the application of e-modules in improving scientific literacy skills. This research employed the quasi-experimental with pretest-posttest control design group. The population of this study was eleventh-grade students of SMA Negeri 1 Anjatan which consisted of 15 classes, specifically seven science classes and eight social studies classes. The research sample was taken using random sampling. The researchers collected the research data using observations and tests. Furthermore, the data was analyzed using ANES software and SPSS v.25. The analyzed data were the prerequisite tests data and the t-test data. The results obtained from students' learning activities show the highest learning activities occurred at the data collection stage. There science literacy skills improvement between the control class and the experimental class was different. The experimental class' N-gain value was 0.30 and the control class' N-gain value was 0.2. Furthermore, the result of the sig statistical tests was 0.000, which was lower than 0.655. Therefore, Ho was rejected and Ha was accepted. It can be concluded that there was an improvement difference between the experimental class and the control class regarding scientific literacy skills.